Frequency of questions in an EFL conversation class - Siti Sarah Fitriani; Kadrina Amilia (Universitas Syiah Kuala, 2017)
This qualitative study was conducted to investigate the types and the purposes of questions used by the teacher in an EFL conversation class. The subject of this study was the English teacher at SMA Lab School Banda Aceh who taught the second graders of XI classes; XIp1, XIp2, XIp3, XIs. Observation form, a set of interview questions and field note were used as the instruments. The questions posed by the teacher in the classroom were then categorized and described in accordance with Brown’s theory (2001) on the two types of questions: display and referential questions. Data from interview were coded in relation to the purpose of asking each question type. The findings showed that apart from Brown’s types of questions, three additional question types were also found. Therefore, a total of five types of question were found viz: display, referential, comprehension check, confirmation check and procedural question. The data from the observations showed that the teacher used more display questions than referential questions. From a total of 259 questions posed by the teacher in the classroom, 120 were display questions (46%), 101 were referential (39%), 17 comprehension checks (6.5%), and 20 procedural questions (8%). Only one confirmation check question (0.4%) was found during the teaching- learning processes. Furthermore, the data from interview exposed the purposes of the teacher asking these questionsviz: to encourage the participation of students in the lesson, to get feedback from them, to encourage them to think and focus, to create a good classroom atmosphere, to stimulate and maintain their interest, and to emphasize certain points in the lesson.